Waste-to-energy power plants: Multi-objective analysis and optimization of landfill heat and methane gas by recirculation of leachate - Khan, Osama; Parvez, Mohd; Yahya, Zeinebou; Alhodaib, Aiyeshah; Yadav, Ashok Kumar; Hoang, Anh Tuan; Agbulut, Umit (ELSEVIER, 2024)
Elevated thermal energy trapped in landfill voids is a potential threat to humans since, fires might get ignited, eventually releasing poisonous gases, contaminated fluids (leachate), and abnormal quantity of heat. This study explores the practical potential of landfills to produce heat and methane gas through a leachate recirculation process, which involves returning nutrient-rich fluids to landfills to maximize electricity generation. This paper presents an experimental investigation of the physio-chemical properties of landfills by recirculating leachate to achieve sustainable performance characteristics of landfill models. Five input parameters i.e. waste particle size (WPS in mm), waste addition (WA in Ktoe), inorganic matter content (IO in %), leachate recirculation rate (LRR in liters/day), and age of landfill (LA in years) each at five levels is considered. The investigation is accomplished on the central composite rotating design (CCRD) matrix with a 5-level factor. The results reveal that WPS at D10, WA at 52.32 Ktoe, IO at 2%, LRR at 300 l/day, and LA at 4.07 year is the optimal setting of the input parameters that produce optimum values of the output responses considered simultaneously. An innovative method is studied for simultaneously lowering the internal temperature of landfills to ideal levels while also enhancing the rate of methane production. Energy transfer to the ORC system is 2.3 GJ in winters while 1.5 GJ in summers. Landfills equipped with leachate recirculation facilities provide 2.2 times more energy with stabilization occurring in 4th year with an energy content of 950 MJ/m3 of waste.
Keywords: Waste to energy; Energy Transfer; Landfill gas; Response Surface Methodology; Sustainable Development; MUNICIPAL SOLID-WASTE; MULTICRITERIA ANALYSIS; MANAGEMENT; RECOVERY; Engineering